THE BLIND ENTREPRENEUR MINDSET IN MANAGING MORE CAFE WYATA GUNA BANDUNG - Muhammad Panji; Yuce Sariningsih (JEES: Journal of Economic Empowerment Strategy, 2023)
The orphanage is one of the solutions to handling every abandoned individual. It helps to improve the child’s welfare a way of educating, taking care of, guiding, giving directions, and providing some skill sets to develop independence for each individual. The independence which is focus of this research is aiming at economic independence where an entrepreneur mindset is expected to develop among the blinds inside the orphanage. This has become an attractive point since the blinds will be guided in strengthening their entrepreneurial spirit. The approach being used is descriptive with the qualitative method. The outcome of this research is to provide useful insights into developing theories related to the social worker’s role in implementing the blind entrepreneur mindset of More Cafe Bandung.